TERMS OF MEDICAL INFORMATION SYSTEM - Elmurotova Dilnoza Bakhtiyorovna; Sayfullayeva Dilbar Izzatillayevna; Isroilova Shaxzoda Adxamjon Qizi (Scholar Express Journals, 2024)
The work discusses the basic definition of a measuring medical information system. It is shown that to study the electrical parameters of a biological object using the influence of a given electrical power, it is necessary to use an information-measuring system based on digital measuring generators of a given electrical power.
Keywords: measuring medical information system; biological object; digital measuring generators of a given electrical power